Prevalence of Hepatitis B Antigen and Antibody in Prostitutes. Issue 5913 (4th May 1974) - Papaevangelou, G.; Trichopoulos, D.; Kremastinou, T.; Papoutsakis, G.
Abstract : We investigated the prevalence of hepatitis B antigen (HBAg) and antibody (HBAb) in 293 prostitutes and in 379 pregnant women of similar age and of low socioeconomic level, who served as controls. HBAg was found in 4·4% of prostitutes and 3·4% of controls. The prevalence of HBAb was significantly higher (P <0·001) in prostitutes (56·7%) than in controls (24·5%). The prevalence of HBAb was clearly age-dependent in both groups. Evidence of hepatitis B virus infection significantly increased with the number of years in prostitution. The evidence of increased infection rates among prostitutes and their distribution support the hypothesis that hepatitis B infection is sexually transmitted.